2013
DOI: 10.1103/physrevlett.111.096801
|View full text |Cite
|
Sign up to set email alerts
|

Localized Many-Particle Majorana Modes with Vanishing Time-Reversal Symmetry Breaking in Double Quantum Dots

Abstract: We introduce the concept of spinful many-particle Majorana modes with local odd operator products, thereby preserving their local statistics. We consider a superconductor -double quantum dot system where these modes can arise with negligible Zeeman splitting when Coulomb interactions are present. We find a reverse Mottinsulator transition, where the even and odd parity bands become degenerate. Above this transition, Majorana operators move the system between the odd parity ground state, associated with elastic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…In the case of a triple QD, assuming 23 . In the case where μ 2 or μ 3 are zero the MFs are spatially separated [25].…”
Section: Undriven Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of a triple QD, assuming 23 . In the case where μ 2 or μ 3 are zero the MFs are spatially separated [25].…”
Section: Undriven Systemmentioning
confidence: 99%
“…In a system where neighboring QDs are coupled through superconducting reservoirs as in Fig. 1, in the limit of large superconducting gap the superconductors can be traced out and an effective Hamiltonian for the dots is obtained [23,24] as…”
Section: Undriven Systemmentioning
confidence: 99%
“…This can be treated as a uniform spin rotation on the respective site, sending truecˆ2σfalse(false)cosfalse(θ/2false)truecˆ2σfalse(false)+σsinfalse(θ/2false)truecˆ2trueσfalse(false). The effective Hamiltonian is then (): rightscriptHnormaleffcenter=leftj,σεjcˆj,σcˆj,σrightcenterleftEnormalZj(cˆj+cˆj+cˆjcˆj)+Ujcˆj+cˆj+cˆjcˆjrightcenterleft+tσ()cosθ2truecˆ1,σtruecˆ2,σthinmathspace+thinmathspaceσsinθ2truecˆ1,σtruecˆ2,trueσthinmathspace+thinmathspaceh.c.rightcenterleft+Δeiφ+/2cos()…”
Section: Derivation Of Effective Hamiltonianmentioning
confidence: 99%
“…Fortunately, these requirements can be strongly relaxed as shown recently by Wright and Veldhorst (), who considered the effect of strong correlations for the engineering of Majorana bound states. They demonstrated that only vanishingly small anisotropic Zeeman splitting, kBT, is required.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effects of time-reversal symmetry breaking can be easily measured by applying a magnetic field [3]. Nowadays, a variety of theoretical and experimental research about small conducting devices, such as QDs, has been the focus of many scientists and engineers attention [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%